A Brief Mobile Evaluative Conditioning App to Reduce Body Dissatisfaction? A Pilot Study in University Women - Kosinski, Thierry (Frontiers in Psychology, 2019)
Objective: Body dissatisfaction is a major risk factor underlying vulnerability to eating disorders. Laboratory settings suggest that body dissatisfaction could be improved by using evaluative conditioning (EC). The present study evaluates the feasibility of using an EC app in everyday life and the effects of its use on body dissatisfaction. Method: We designed a game-like app inspired by the Therapeutic Evaluative Conditioning app. 60 participants were randomly assigned to two conditions. Participants in the EC condition had to pair photographs of their own body with positive photographs, while participants in the neutral condition had to pair photographs of their own body with neutral photographs. We tested the effect of use of the app on body dissatisfaction, drive for thinness, self-esteem, mood and eating behaviors. Results: Analysis revealed that participants in all conditions presented a significant decrease in body dissatisfaction and drive for thinness. However, contrary to our hypothesis, these reductions were not greater in the EC condition than in the neutral condition. Conclusions: This is the first study to evaluate the effects of an app-based EC intervention targeting body image. Results appear to be promising and the app could easily be implemented in an ecological setting as it is a low effort, attractive and accessible intervention. However, these findings do not support the idea that evaluative conditioning is responsible for the effects. Results are discussed.